The role of the L-arginine-NO-cGMP pathway in the development of tolerance to mephedrone-induced hyperlocomotion in mice - Bielecka-Papierz Gabriela; Poleszak Ewa; Szopa Aleksandra; Listos Joanna; Orzelska-Gorka Jolanta; Jakobczuk Małgorzata; Baluk Kamila; Talarek Sylwia; Serefko Anna (Current Issues in Pharmacy and Medical Sciences, 2023)
The tendency of a psychostimulant to increase locomotion in rodents is considered to be associated with its addictive properties. Mephedrone, one of the most popular psychoactive substances used recreationally, is known to enhance locomotor activity in mice, but little is known about the potential development of tolerance to its central effects. In the present study, we decided to evaluate the possible involvement of the L-arginine-NO-cGMP pathway in the development of tolerance to mephedrone-induced hyperlocomotion. Experiments were performed on adult male Albino Swiss mice, and the locomotor activity was measured automatically. Our work indicated that a 5-day administration of L-NAME (25 or 50 mg/kg/day), methylene blue (5 or 10 mg/kg/day), and L-arginine hydrochloride (i.e., 250 mg/kg/day) prevented the development of tolerance to mephedrone-induced (5 mg/kg/day) hyperlocomotion, whereas treatment with L-arginine hydrochloride at a dose of 125 mg/kg/day potentiated the development of tolerance to this central effect of mephedrone. Summarizing, our data revealed that the L-arginine-NO-cGMP pathway contributes to the development of tolerance to mephedrone’s central effects since inhibition of this signalling via blocking of NOS or NO-stimulated sGC prevented the development of tolerance to mephedrone-induced hyperlocomotion. As for cGMP-regulated phosphodiesterases, most probably they are not involved in these mechanisms.